¿Combatividad encauzada o recomposición del trabajo organizado? La dinámica de la negociación colectiva en los gobiernos kirchneristas - Cecilia Anigstein (Les Cahiers ALHIM)
The quantitative growth of collective bargaining, the expansion of its coverage, and the restoration of the pattern bargaining by industry as priority wage policy instrument, in recent years in Argentina, all implied a discontinuity in relation to the dynamics of the previous period, which had taken place in an inflationary context. Nevertheless, it should be considered that the neoliberal legacy has imposed limits to this process. Mainly, the consolidated presence of social fractions that are outside the frontiers of collective right. Those limits affect the associated workers, since the individualisation mechanisms of labor relations integrated on collective bargaining agreements during the peak of neoliberal politics have been neither excluded nor deeply reversed. Also, unilaterally attributing the growth of wage bargaining to the inflationary process or thinking of it as an instrument for the regulation of labor conflicts could lead to an underestimation of the role played by associated and non-associated workers. This work describes the dynamics of collective bargaining between 2004 and 2010, and explores the role that the organised labor movement has played on this process.